Biomimetic Nanofur: Nanofur for Biomimetic Applications (Adv. Mater. Interfaces 4/2014). Issue 4 (July 2014) - Röhrig, Michael; Mail, Matthias; Schneider, Marc; Louvin, Henri; Hopf, Andreas; Schimmel, Thomas; Worgull, Matthias; Hölscher, Hendrik
<x xml:space="preserve">Abstract</x> Nanofur is produced by hot pulling, a highly scalable molding technique for the fabrication of biomimetic surfaces densely covered with nanohair. This nanofur can be used for various biomimetic applications, such as self‐healing, air retention, and oil‐water separation as demonstrated by H. Hölscher and co‐workers in article 1300083. The SEM image shows the fractal surface topography of nanofur fabricated from polycarbonate. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>